A Case Report of Eosinophilic Esophagitis Accompanying Hypereosinophilic Syndrome. (1st August 2012) - Jawairia, Mahreema; Shahzad, Ghulamullah; Singh, Jaspreet; Rizvon, Kaleem; Mustacchia, Paul
Abstract : Hypereosinophilic syndrome is a blood disorder characterized by the overproduction of eosinophils in the bone marrow with persistent peripheral eosinophilia, associated with organ damage by the release of eosinophilic mediators. Although HES can involve multiple organ systems, GI tract involvement is very rare. Few cases of HES presenting with gastritis or enteritis have been reported worldwide. To date, HES presenting with esophagus involvement has only been reported once. Here, we present a 39-year-old Hispanic female patient with history of HES presenting with complaints of dysphagia and generalized pruritus.